CULTURAL IMPLEMENTATION OF COURAGEOUS COMMUNICATION THROUGH THE INDONESIAN LANGUAGE IN BOARDING SCHOOLS - Ilmani, Yulia Rahmi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Education is one of the factors that determine and influence social change. Through education, it is hoped that it can produce the next generation who have a strong character to receive the baton of national leadership. In order to realize the achievement of pesantren culture in forming Indonesian-language politeness for students at the Nurul Amin Islamic Boarding School. This research uses qualitative research with a descriptive approach using interviews, data collection, document analysis and observation. This study aims to analyze and understand the formation of pesantren culture in Indonesian-language politeness in Islamic boarding schools. The results showed that; Santri Pondok Pesantren Nurul Amin speaks politely, well and correctly.